2011
DOI: 10.1128/aac.01092-10
|View full text |Cite
|
Sign up to set email alerts
|

The Antibiotic Monensin Causes Cell Cycle Disruption ofToxoplasma gondiiMediated through the DNA Repair Enzyme TgMSH-1

Abstract: Monensin is a polyether ionophore antibiotic that is widely used in the control of coccidia in animals. Despite its significance in veterinary medicine, little is known about its mode of action and potential mechanisms of resistance in coccidian parasites. Here we show that monensin causes accumulation of the coccidian Toxoplasma gondii at an apparent late-S-phase cell cycle checkpoint. In addition, experiments utilizing a monensinresistant T. gondii mutant show that this effect of monensin is dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 38 publications
(45 reference statements)
6
37
0
Order By: Relevance
“…The effect of F1792-0016 on histone-related transcript levels is very similar to that observed previously for monensin, which was found to have potent antiToxoplasma activity. Microarray analyses of monensin-treated parasites resulted in increased abundances of some of the same transcripts that are upregulated in the presence of F1792-0016, particularly members of the histone family (H2, H3, and H4) (36). Consistent with this observation, monensin also increases the number of parasites that are in the S/M phase of the cell cycle (36).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The effect of F1792-0016 on histone-related transcript levels is very similar to that observed previously for monensin, which was found to have potent antiToxoplasma activity. Microarray analyses of monensin-treated parasites resulted in increased abundances of some of the same transcripts that are upregulated in the presence of F1792-0016, particularly members of the histone family (H2, H3, and H4) (36). Consistent with this observation, monensin also increases the number of parasites that are in the S/M phase of the cell cycle (36).…”
Section: Discussionsupporting
confidence: 52%
“…9). This suggests that a possible mechanism of action for F1792-0016 may be to arrest parasites in the S/M phase of the cell cycle, as has been seen with other inhibitors of T. gondii growth, such as monensin (36). Previously, mutants resistant to the antibiotic monensin were identified, and we also examined whether one such mutant (MSH-1) was also resistant to F1792-0016 and found that it was equally susceptible to F1792-0016 as a wild-type strain (for both strains, 48 h of F1792-0016 exposure resulted in 40% S/M parasites, compared to 29% in controls; P Ͼ 0.05).…”
Section: F1792-0016 Destroys Parasite-containing Vacuolesmentioning
confidence: 89%
See 2 more Smart Citations
“…Recent reports highlighted their activity against Trypanosoma brucei, Toxoplasma gondii, and cytomegalovirus (33)(34)(35)(36). Considerable attention has been devoted recently to salinomycin and derivatives due to their selective activity against tumor stem cells (13,37,38).…”
Section: Discussionmentioning
confidence: 99%